Monitoring the efficacy of drugs for neglected tropical diseases controlled by preventive chemotherapy. Issue 4 (December 2015) - Albonico, M.; Levecke, B.; LoVerde, P.T.; Montresor, A.; Prichard, R.; Vercruysse, J.; Webster, J.P.
Highlights: Scale-up in drug donations for control of NTD subject to PC calls for monitoring drug efficacy. Monitoring efficacy of anthelmintics should be a component of any NTD control program. NTD disease-specific models to predict impact of PC and detect outliers should be developed. Research studies to identify resistance markers for all NTD drugs are urgently needed. Development of drugs combinations as well as of new drug entities for NTD is a priority. Abstract: In the last decade, pharmaceutical companies, governments and global health organisations under the leadership of the World Health Organization (WHO) have pledged large-scale donations of anthelmintic drugs, including ivermectin (IVM), praziquantel (PZQ), albendazole (ALB) and mebendazole (MEB). This worldwide scale-up in drug donations calls for strong monitoring systems to detect any changes in anthelmintic drug efficacy. This review reports on the outcome of the WHO Global Working Group on Monitoring of Neglected Tropical Diseases Drug Efficacy, which consists of three subgroups: (i) soil-transmitted helminthiases (ALB and MEB); (ii) onchocerciasis and lymphatic filariasis (IVM); and (iii) schistosomiasis (PZQ). Progress of ongoing work, challenges and research needs for each of the four main drugs used in helminthic preventive chemotherapy (PC) are reported, laying the ground for appropriate implementation of drug efficacy monitoring programmes under the co-ordination and guidelines of the WHO. Best practices for monitoring drug efficacy should be made available and capacity built as an integral part of neglected tropical disease (NTD) programme monitoring. Development of a disease-specific model to predict the impact of PC programmes, to detect outliers and to solicit responses is essential. Research studies on genetic polymorphisms in relation to low-efficacy phenotypes should be carried out to identify markers of putative resistance against all NTD drugs and ultimately to develop diagnostic assays. Development of combination and co-administration of NTD drugs as well as of new drug entities to boost the armamentarium of the few drugs available for NTD control and elimination should be pursued in parallel.